An Observational Evaluation of Primary Care Online Resources - Pablo Millares Martin; Jorge Millares-Bobet (European Medical Journal, 2023)
Background: General practice websites are getting more relevant as more interaction with patients is occurring digitally; however, there are no regulations governing them, nor much research about their benefit or quality. Objectives: To understand the online presence of general practices through time, using a tool developed for this purpose and assessing practices’ websites at two separate times. Methods: A form was developed to assess websites on base of their performance against 17 parameters, including information about the practice (logo, interactive address, area covered, telephone, opening times, details about staff, and quality rate), website parameters (number of pages and links on the site, level of link errors, loading speed, and search engine), and online services provided (social media, interactions like messaging, booking appointments, ordering prescriptions, accessing medical records, and allowing video consultations). Possible scores ranged from 17–66 points, with two to four points per factor analysed. A lower score was a mark of quality. Results: Practices were scored twice over the last 5 years; however, the sample average, although improving from 36.5 to 31.6, still puts practices websites midway in the quality range of the tool used. Looking at individual parameters, the homepage’s average loading time deteriorated, as well as maps showing the practice location. However, other details improved. Conclusions: Websites are taking a more relevant role in healthcare interactions, but their quality has improved little in the last 5 years. There is a need for stricter regulations if the digital presence of primary care is expected to play a safe role in primary care provision.